Predictors of quality of life of medical students and a comparison with quality of life of adult health care workers in Thailand - Angkurawaranon C. (2017)
© 2016, The Author(s). Introduction: There have been few studies which have compared the quality of life between medical students and adult health care workers. Aims: (1) To compare health related quality of life (HRQoL) between medical students and adult health care workers and (2) to identify factors associated with quality of life of medical students. Methods: A cross sectional survey of medical students at Chiang Mai University and health care workers at Chiang Mai University Hospital in 2013. Results: Compared with the population of adult health care workers, medical students had a higher physical HRQoL but similar mental HRQoL. This is potentially mediated by the presence of depression, as the prevalence of depressive symptoms was similar in both groups. Higher academic achievement and absence of underlying biomedical conditions were associated with higher HRQoL in medical students. Conclusion: The psychological burden for medical students in Thailand could be at similar levels to that of their adult health care counterparts.